Athletic cognitive motivation and its relationship to perform some duties within the defensive formations of the region for handball players aged (15-17) years - Ibtisam Saleem (physical education and sport sciences college for women/ Baghdad University, 2020)
The study aimed to identify the athletic cognitive motivation and its relationship in the performance of some duties within the defensive formations of the region for handball players aged 15-17 years, and the researcher used the descriptive approach to suit the nature of the research problem on a sample of (24) players from the National Center for Talent Care Sports handball of the Ministry of Youth and Sports / Baghdad for the season (2018-2019) and ages (15-17) years and the total number (34) player, and the researcher used the scale of sports knowledge motivation prepared by Al-Badrani (2012), and conducting a handball match, and used The appropriate statistical means for data processing are: The players of the National Center for Sports Talent Care have athletic cognitive motivation and a significant correlation between the athletic cognitive motivation and the performance of some duties within the defensive formations of the region and recommended the necessity of adopting appropriate methods, which work to stimulate the motivation to reach the best performance. Keywords: - athletic cognitive motivation - Defensive handball duties